Recent advances of DNA methylation in osteonecrosis of the femoral head - Zhou, Tingting; Liu, Huan; Li, Huayan; Zhang, Yan; Li, Xiaoming (Frontiers in Genetics, 2025)
DNA methylation, maintenance, and demethylation are essential for maintaining normal physiological functions. Recent studies have revealed that DNA methylation plays a crucial role in the progression of osteonecrosis of the femoral head. DNA methylation regulates the differentiation direction of bone marrow mesenchymal stem cells, affects angiogenesis, and is involved in the proliferation and apoptosis of osteocytes, holding significant potential for early diagnosis and treatment of the disease. This paper introduces the concept and process of DNA methylation, with an emphasis on its molecular mechanisms in osteonecrosis of the femoral head. Furthermore, we propose that modulating different states of DNA methylation, such as inhibiting the function of DNA methyltransferases to induce DNA demethylation, could impact the disease progression of osteonecrosis of the femoral head, offering new insights for its treatment.